Answer:
8y^3+6y^2-29y+15
Step-by-step explanation:
the correct expression is
(4y − 3)(2y^2 + 3y − 5)
Given data
We have the expression
(4y − 3)(2y^2 + 3y − 5)
let us open bracket
8y^3+12y^2-20y-6y^2-9y+15
Collect like terms
8y^3+12y^2-6y^2-20y-9y+15
8y^3+6y^2-29y+15
i believe the answer is B
but i could always be wrong :(
Answer:
y = 4 + -2x
Step-by-step explanation:
Simplifying
y = -2x + 4
Reorder the terms:
y = 4 + -2x
Solving
y = 4 + -2x
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Simplifying
y = 4 + -2x
-2 1/2 / 6 would be -5/12, just turn - 2 1/2 into a decimal and divide by 6 :)
The value of m is -30 because once you get m on the one side the equation is 3m=-90 and once you divide -90 by 3 you get m=-30.